Licochalcone-A induces intrinsic and extrinsic apoptosis via ERK1/2 and p38 phosphorylation-mediated TRAIL expression in head and neck squamous carcinoma FaDu cells. (March 2015) - Park, Mi-Ra; Kim, Su-Gwan; Cho, In-A.; Oh, Dahye; Kang, Kyeong-Rok; Lee, Sook-Young; Moon, Sung-Min; Cho, Seung Sik; Yoon, Goo; Kim, Chun Sung; Oh, Ji-Su; You, Jae-Seek; et al.
Graphical Abstract: Highlights: Licochalcone-A is cytotoxic, inducing cell death in FaDu cells, but does not affect human normal oral keratinocytes. Licochalcone-A-induced cell death of FaDu cells is mediated by both extrinsic and intrinsic apoptotic signaling pathways. Licochalcone-A-induced apoptosis of FaDu cells is triggered by TRAIL expression induced by ERK1/2 and p38 MAPK. Abstract: We investigated Licochalcone-A (Lico-A)-induced apoptosis and the pathway underlying its activity in a pharyngeal squamous carcinoma FaDu cell line. Lico-A purified from root of Glycyrrhiza inflata had cytotoxic effects, significantly increasing cell death in FaDu cells. Using a cell viability assay, we determined that the IC50 value of Lico-A in FaDu cells was approximately 100 µM. Chromatin condensation was observed in FaDu cells treated with Lico-A for 24 h. Consistent with this finding, the number of apoptotic cells increased in a time-dependent manner when FaDu cells were treated with Lico-A. TRAIL was significantly up-regulated in Lico-A-treated FaDu cells in a dose-dependent manner. Apoptotic factors such as caspases and PARP were subsequently activated in a caspase-dependent manner. In addition, levels of pro-apoptotic factors increased significantly in response to Lico-A treatment, while levels of anti-apoptotic factors decreased. Lico-A-induced TRAIL expression was mediated in part by a MAPK signaling pathway involving ERK1/2 and p38. In xenograft mouse model, Lico-A treatment effectively suppressed the growth of FaDu cell xenografts by activating caspase-3, without affecting the body weight of mice. Taken together, these data suggest that Lico-A has potential chemopreventive effects and should therefore be developed as a chemotherapeutic agent for pharyngeal squamous carcinoma.